A Novel Approach in Hybrid Energy Storage System for Maximizing Solar PV Energy Penetration in Microgrid. (22nd January 2022) - Amirthalakshmi, T. M.; Ramesh, S.; Prabu, R. Thandaiah; Ramkumar, G.; Sahoo, Satyajeet; Thomas, Prince; Ramalingam, R. Jothi; Al-Lohedan, Hamad; Al-Dhayan, Dhaifallah M.; Sureshkumar, Shanmugam
Abstract : Nowadays, energy storage system is utilized in many countries for energy planning in the future. The changes in solar radiation lead to the overproduction of electricity in a solar photovoltaic generator. A hybrid energy storage system would play an important role in enhancing the reliability of power generation using the solar system. The microgrid is the indispensable infrastructure of the smart grid in photovoltaic systems. In this paper, the energy storage system within the microgrid of the PV system is analysed. The storage system configuration and topologies of the microgrid are analysed with power electronic interference, control scheme, and optimization of the renewable source and energy storage system. A general sizing technique for HESS in a PV system based on pinch analysis and design space. The size of HESS scales that connect generator ratings to storage capacity is created by utilizing the pinch analysis on load and resource data. The design space is a feasible combination of a short-, long-, and medium-sized energy storage system in a PV generator.